The Synthesis, Characterization and Anti-corrosive Properties of Doped Hydroxyapatite - Šimková, Lenka; Šulcová, Petra (Univerzita Pardubice, 2020)
The aim of this work is to investigate and evaluate the effect of precipitation conditions on the synthesis of hydroxyapatite, then to study of partial substitution of calcium ions by selected elements (such as magnesium, zinc, aluminum, and strontium) and characterize physicochemical properties of doped hydroxyapatite phase.
Syntéza, charakterizace a antikorozní vlastnosti substituovaného hydroxyapatitu
Keywords: precipitation; substitution; XRD; SEM; preliminary corrosion test; srážení; substituce; XRD; SEM; předběžný korozní test